2010
DOI: 10.3109/13880209.2010.499130
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of oleanolic acid on cerebral ischemic damagein vivoand H2O2-induced injuryin vitro

Abstract: These results demonstrate that oleanolic acid effectively alleviates cerebral ischemic damage in vivo and oxidative injury in vitro, which may be in part due to the modulation of endogenous antioxidants and the improvement of mitochondrial function. Oleanolic acid may be a potential medicine for attenuating ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…The mechanism is possibly attributed to activating Nrf2/HO-1 pathway. More recently, triterpenoids structurally similar to KBA, such as maslinic acid and oleanolic acid, have been reported to significantly increase Nrf2, leading to neuroprotection [20,11]. In another approach, stimulating Nrf2 by triterpenoid could effectively reduce 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced oxidative stress in the mouse model while Nrf2 knockout mice failed to block against MPTP neurotoxicity, implying a direct protective role of Nrf2/ARE against MPTP neurotoxicity [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism is possibly attributed to activating Nrf2/HO-1 pathway. More recently, triterpenoids structurally similar to KBA, such as maslinic acid and oleanolic acid, have been reported to significantly increase Nrf2, leading to neuroprotection [20,11]. In another approach, stimulating Nrf2 by triterpenoid could effectively reduce 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced oxidative stress in the mouse model while Nrf2 knockout mice failed to block against MPTP neurotoxicity, implying a direct protective role of Nrf2/ARE against MPTP neurotoxicity [21].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective property of pentacyclic triterpenoid has drawn increasing interest during the past couple of years. By way of example, oleanolic acid shows protective effects on cerebral ischemic damage and H 2 O 2 -induced injury in vitro [11]. Similarly, ursolic acid, a naturally occurring pentacyclic triterpenoid, was reported to promote the neuroprotection after cerebral ischemia in mice by activating Nrf2 pathway [12].…”
Section: Introductionmentioning
confidence: 98%
“…The intraperitoneal administration of safranal (11) improved all these previous oxidative stress markers. Moreover, the triterpene oleanolic acid (105) acting as antioxidant attenuated the increased level of oxidative stress and the decline of mitochondrial function observed in hydrogen peroxide-treated PC12 cells and that produced as a consequence of cerebral ischemic in rats [54].…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Cells protect themselves from oxidative damage through free radical scavenging systems such as enzymatic [catalase, superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px)] and nonenzymatic (flavonoids, vitamin C, and vitamin E) (Sies & Murphy, 1991;Mostafa et al, 2006). Countless studies have shown antioxidant therapies could be effective in preventing ischemia/reperfusion injury Khan et al, 2007;Rong et al, 2011). Therefore, administration of antioxidants could give potential benefit by enhancing the activities of antioxidant enzymes or scavenging free radicals and was used as a protection strategy to alleviate ischemia/reperfusion…”
Section: Introductionmentioning
confidence: 99%